Democratization of Health Services: Dynamics of Administrative Resistances (N'weti - comunicação para saúde, 2019)
This policy brief, apart from describing the dilemmas of the democratization process of health services it, aims to analyze its implications on the dynamics of social accountability in the health sector and, finally, to inform on possible ways for a more coherent democratization, considering the normative discourses
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; decentralization / descentralização; health / saúde

Sound of One Hand Clapping: Information Disclosure for Social and Political Action for Accountability in Extractive Governance in Mozambique - Awortwi, Nicholas; Nuvunga, Adriano (IDS, 2019)
Corruption through opaque public contracts costs Africa billions of dollars in revenue loss annually. Globally, initiatives to address this have centred on information disclosure (ID) but under what conditions does it work to promote accountability in the extractive sector that for a long time has seen its revenue management as being a major cause of conflict in Africa? Our study on this issue in Mozambique reveals intriguing findings, which suggest that protagonists of ID would need to recalibrate their strategies for promoting accountability. The study on ID in extractive governance in Mozambique has found 17 factors that connect to result in citizen and institutional inaction in demanding government accountability. The lessons from the study for policy and practice are that unless there is a link between ID and a government’s reputation, which scales up to the risk of a ruling government losing power, accountability is unlikely to occur when new information is disclosed.
Accepted: 2019-01-28T16:38:12Z ISSN: 2040-0209
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; corruption / corrupção; decentralization / descentralização; extractive industries / indústrias extractivas; natural resources / recursos naturais

Relatório De Diagnóstico Sobre Transparência, Governação E Corrupção - República de Moçambique (International Monetary Fund (IMF), 2019)
A economia de Moçambique encontra-se num ponto de viragem, e os esforços para abordar as vulnerabilidades em matéria de governação e corrupção podem ter um impacto positivo duradouro. Já tomámos medidas para abordar as vulnerabilidades em matéria de governação e corrupção. Contudo, reconhecemos que subsistem falhas em diversas áreas relevantes da economia. A fim de abordar algumas das debilidades restantes, temos reformas de governação em curso e em perspectiva em várias áreas, muitas delas apoiadas por diversos doadores. Reconhecemos que a implementação eficaz continua a suscitar preocupações. Reconhecemos que a falta de transparência pode igualmente exacerbar as preocupações com a governação e agravar o risco de conflitos de interesse. Embora reconheçamos que temos um papel essencial a cumprir na melhoria da governação e no combate à corrupção, não podemos fazê-lo sozinhos. Estamos preparados e dispostos a tomar medidas concretas.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; corruption / corrupção; transparency / transparência

Citizen engagement in public services in low- and middle-income countries: A mixed-methods systematic review of participation, inclusion, transparency and accountability (PITA) initiatives - Waddington, Hugh; Sonnenfeld, Ada; Finetti, Juliette; Gaarder, Marie; John, Denny; Stevenson, Jennifer (Campbell Systematic Reviews, 2019)
Background How do governance interventions that engage citizens in public service delivery planning, management and oversight impact the quality of and access to services and citizens’ quality of life? This systematic review examined high quality evidence from 35 citizen engagement programmes in low- and middle-income countries that promote the engagement of citizens in service delivery through four routes: participation (participatory priority setting); inclusion of marginalised groups; transparency (information on rights and public service performance), and/or citizen efforts to ensure public service accountability (citizen feedback and monitoring); collectively, PITA mechanisms. We collected quantitative and qualitative data from the included studies and used statistical meta-analysis and realist-informed framework synthesis to analyse the findings. Results The findings suggest that interventions promoting citizen engagement by improving direct engagement between service users and service providers, are often effective in stimulating active citizen engagement in service delivery and realising improvements in access to services and quality of service provision, particularly for services that involve direct interaction between citizens and providers. However, in the absence of complementary interventions to address bottlenecks around service provider supply chains and service use, citizen engagement interventions alone may not improve key wellbeing outcomes for target communities or state-society relations. In addition, interventions promoting citizen engagement by increasing citizen pressures on politicians to hold providers to account, are not usually able to influence service delivery. Conclusions The citizen engagement interventions studied were more likely to be successful: (1) where the programme targeted a service that citizens access directly from front-line staff, such as healthcare, as opposed to services accessed independently of service provider staff, such as roads; (2) where implementers were able to generate active support and buy-in for the intervention from both citizens and front-line public service staff and officials; and (3) where the implementation approach drew on and/or stimulated local capacity for collective action. From a research perspective, the review found few studies that investigated the impact of these interventions on women or other vulnerable groups within communities, and that rigorous impact evaluations often lack adequately transparent reporting, particularly of information on what interventions actually did and how conditions compared to those in comparison communities.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/cl2.1025
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização

Introduction: The Accountability Politics of Reducing Health Inequalities: Learning from Brazil and Mozambique - Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P.; Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P. (Novos estudos CEBRAP, 2019)
Inequality is a key political issue of our times. It has political consequences, fuelling conflict and raising legitimacy chal‑ lenges for regimes around the world, in democratic and non‑demo‑ cratic settings alike. At the centre of these challenges is the question of accountability: who can be held accountable, on what basis, how and by whom for tackling or failing to tackle which inequalities. In the field of global health, inequality has long been a key issue. A significant body of work — in global health and health systems research — has approached the issue of health inequalities and in‑ equities by highlighting the role of social determinants (Marmot, 2015; Wilkinson; Pickett, 2006; Barreto, 2017). A more recent and less developed stream of work frames them in terms of political de‑ terminants: in other words, seeing them as issues that may be ad‑ dressed through politics as well as policy.
Publisher: Centro Brasileiro de Análise e Planejamento
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde